ANALISA POTENSI TEGAKAN HASIL INVENTARISASI HUTAN DI KPHP MODEL BERAU BARAT - Andhi Trisna Putra (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Potential Analysis of Forest Stand Inventory Results in Forest Management Unit (KPH) Pilot Berau Barat, East Kalimantan. The purpose of this study was to determine the potential , the structure and species composition of forest stands in KPHP Berau Barat for one of the basic preparation of forest governance and management of the plan .This study uses data from forest inventories KPHP models that do BPKH Region IV Samarinda in September 2012 then processed and updated with secondary data in March 2014. Tally sheet data from the field and then put together and categorized based on the growth rate , diameter class and species group . From the results of the consistency of the data is then calculated stem volume , tree coordinates . Secondary data include the general state of the location , the function of forests , forest management history , regional geophysical information and information about social culture . It is also seeking written information such as books, reports, journals and interviews with management KPHP Berau Barat.The results obtained are 1) The species composition in small trees and trees in KPHP Berau Barat area dominated by groups of Meranti with average 90.69 stems per hectare; 2) Retrieved 84 kinds of plants with a total of 11 818 individuals , comprising 1,113 seedlings , saplings 1,262 , 4,168 poles and 5,275 trees; 3) At the level of seedling types Meranti group dominates the average 2006.31 seedlings per hectare . Of saplings and poles average number per hectare is dominated by a mixed forest wood types for each - 634.15 and 315.53 respectively per hectare . At the tree level dominated by meranti group with 53.49 stems per hectare ; 4 ) At the level of the tree is the dominant species with 1,319 types of stem Meranti , Medang of 545 rods and Guava 378 rods . While the average volume - average per hectare or so-called greatest potential is the kind of kind of Meranti with 55.929 m3/ha ,Medang m3/ha at 13.230 and 12.574 Keruing m3/ha ; 5 ) At the seedlings obtained INP is the biggest meranti is 53.19 % , Guava by 20.84 % and 16.71 % Medang. Highest INP of saplings on the type of Meranti at 49.60 % , Guava 27.42 % and 13.79 % Medang At the highest level mast INP obtained on the type of Meranti at 64.64 % , Guava 26.77 % and 25.77 % Mendarahan . At the level of the tree has the largest INP Meranti 75.01 % ,Medang 31% and Guava 21.50 %.